2017
DOI: 10.3389/fpsyg.2017.01527
|View full text |Cite
|
Sign up to set email alerts
|

How Followers Differing in Career Motivation Gain Career Profits from Transformational Leaders: A Longitudinal Moderated Mediation Model

Abstract: Although, transformational leadership is among the most thoroughly examined leadership theories, knowledge regarding its association with followers' career outcomes is still limited. Furthermore, the underlying mechanisms explaining how transformational leaders affect their employees' career success are yet not well-understood. Based on theoretical assumptions about the processes involved in setting the goal of “making a career,” we propose an indirect effect of transformational leadership on subjective and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The current study expands on the theoretical understanding of SCS in the hospitality industry in two folds. First, the study extends the previous research on the role of transformational leadership in the SCS of employees (Baethge et al ., 2017) by explaining the mediating role of PCB. This reinforces the importance of leadership in inspiring team members to take proactive actions to achieve goals and outcomes in life (Aslam et al ., 2021; Hernaus et al ., 2019).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The current study expands on the theoretical understanding of SCS in the hospitality industry in two folds. First, the study extends the previous research on the role of transformational leadership in the SCS of employees (Baethge et al ., 2017) by explaining the mediating role of PCB. This reinforces the importance of leadership in inspiring team members to take proactive actions to achieve goals and outcomes in life (Aslam et al ., 2021; Hernaus et al ., 2019).…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, organizations in the hospitality industry need to investigate the mechanism of antecedents of SCS, a critical employee outcome (Stumpf, 2014; Abele et al ., 2016). This study found that transformational leadership significantly influences the SCS of employees and supports the previous studies (Al-hussami et al ., 2018; Baethge et al ., 2017) and examines the mechanism of the transformational leadership–career success relationship. Furthermore, this study accepts hypothesis H1 since PCB mediates the positive relationship between transformational leadership and SCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees' subjective career success is especially influenced by their perceptions and reactions to their current jobs and organizations (Ng et al, 2005 ; Ng and Feldman, 2014 ; Baethge et al, 2017 ; Moon and Choi, 2017 ; Peng et al, 2019 ). Therefore, particular attention must be paid to the issue of work engagement in relation to job perception.…”
Section: Introductionmentioning
confidence: 99%